(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Cristianawati O, Sabdaningsih A, Becking LE, Khoeri MM, Nuryadi H, Sabdono A, Trianto A, Radjasa OK. 2019. Biological activity of sponge-associated fungi from Karimunjawa Islands, Indonesia against pathogenic Streptococcus pneumoniae. Biodiversitas 20: 2143-2150. Threats of drug-resistant Streptococcus pneumoniae and the urgent need for new antibiotics require prompt and sustained action for discovering bioactive compounds. This study aimed to isolate sponge-associated fungi as a candidate for sources of drugs. The sponge-associated fungi were screened against the MDR S. pneumoniae. The Deoxyribonucleic Acid (DNA) of fungal isolates that showed the most active was generated by using universal primers ITS1 and ITS4. While the sponge host was identified based on the molecular and by slide section. Out of twenty-nine fungal isolates from 13 marine sponges, S.06.2 isolate produced secondary metabolite that inhibiting the growth of MDR S. pneumoniae. Molecular identification based on the ITS region revealed that the active fungal isolate was closely related to Curvularia lunata, with a 99% similarity. The C. lunata S.06.2 was isolated from sponge Cinachyrella australiensis. Thus, C. lunata S.06.2_ LC315806 can serve as a fruitful strategy for the discovery of novel antibiotics for the treatment of MDR S. pneumoniae.